Molecular characterization and transcriptional regulation analysis of the Torreya grandis squalene synthase gene involved in sitosterol biosynthesis and drought response - Zhang, Feicui; Kong, Congcong; Ma, Zhenmin; Chen, Wenchao; Li, Yue; Lou, Heqiang; Wu, Jiasheng (Frontiers in Plant Science, 2023)
The kernel of Torreya grandis cv. Merrillii (Cephalotaxaceae) is a rare nut with a variety of bioactive compounds and high economic value. β-sitosterol is not only the most abundant plant sterols, but also possesses various biological actions such as antimicrobial, anticancer, anti-inflammatory, lipid lowering effect, antioxidant and anti-diabetic activities. In this study, a squalene synthase gene of Torreya grandis, TgSQS, were identified and functionally characterized. TgSQS encodes a deduced protein of 410 amino acids, prokaryotic expression of TgSQS protein could catalyze farnesyl diphosphate to produce squalene. Transgenic Arabidopsis plants overexpressing TgSQS showed a significant increase in the content of both squalene and β-sitosterol, moreover the drought tolerance of which were also stronger than that of wild type. Transcriptome data of Torreya grandis seedlings showed that the expression level of sterol biosynthesis pathway related genes such as HMGS, HMGR, MK, DXS, IPPI, FPPS, SQS, and DWF1 were all increased significantly after drought treatment. We also proved that TgWRKY3 directly bound to the TgSQS promoter region and regulate its expression through yeast one-hybrid experiment and dual luciferase experiment. Together these ﬁndings demonstrate that TgSQS has a positive role on β-sitosterol biosynthesis, and defense against drought stress, highlighting its importance as a metabolic engineering tool for simultaneous improvement of β-sitosterol biosynthesis and drought tolerance.